2012
DOI: 10.1186/1471-2180-12-229
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of Burkholderia mallei and Burkholderia pseudomalleiby intact cell Matrix-assisted Laser Desorption/Ionisation mass spectrometric typing

Abstract: BackgroundBurkholderia (B.) pseudomallei and B. mallei are genetically closely related species. B. pseudomallei causes melioidosis in humans and animals, whereas B. mallei is the causative agent of glanders in equines and rarely also in humans. Both agents have been classified by the CDC as priority category B biological agents. Rapid identification is crucial, because both agents are intrinsically resistant to many antibiotics. Matrix-assisted laser desorption/ionisation mass spectrometry (MALDI-TOF MS) has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 40 publications
2
43
0
2
Order By: Relevance
“…Additionally, the authors reported that spectra generated from B. mallei exhibited higher levels of homogeneity than did those from B. pseudomallei, with the type strain of B. pseudomallei being separated from more recent isolates of B. pseudomallei. This may be due to genetic modification of the type strain due to significant passage or inappropriate medium combinations (205). This finding represents a potential challenge with regard to standardization of specimen age and levels of manipulation of microbes submitted for MALDI-TOF MS identification.…”
Section: Finally Mencacci Et Al Recognized the Potential Of Maldimentioning
confidence: 98%
“…Additionally, the authors reported that spectra generated from B. mallei exhibited higher levels of homogeneity than did those from B. pseudomallei, with the type strain of B. pseudomallei being separated from more recent isolates of B. pseudomallei. This may be due to genetic modification of the type strain due to significant passage or inappropriate medium combinations (205). This finding represents a potential challenge with regard to standardization of specimen age and levels of manipulation of microbes submitted for MALDI-TOF MS identification.…”
Section: Finally Mencacci Et Al Recognized the Potential Of Maldimentioning
confidence: 98%
“…Overall, novel skills for particular and rapid identification of microorganisms are a very important step toward a appropriate treatment of infectious diseases in veterinary and medical diagnostics and are of major concern today (Hays and Leeuwen, 2012). Identification of different pathogens with mass spectrometry has been known as a technique for acurate and quick recognation of bacteria (Giebel et al, 2010;Karger et al, 2012). Consequently, the most commonly applied technique for mass spectral identification of microorganisms is Matrix Assisted Laser Desorption Ionization Time-Of-Flight Mass Spectrometry (MALDI-TOF-MS) (Biswas and Rolain, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…B. pseudomallei matched Biotyper scores at the species-level threshold (Ͼ2.0) based on the Bruker database, which was only slightly higher than that for the related SSBA bacterial species, Burkholderia mallei ( Table 1). The local database produced higher match scores for B. pseudomallei, and we plan to expand the local MSP entries, as previous studies have recommended the use of an appropriate supplemental reference library for the genus Burkholderia (17).…”
mentioning
confidence: 99%